Characterization of Membranes for Flow Batteries - Kerres, Jochen; Mans, Nico; Krieg, Henning (wiley, 2023)
In this chapter, the most commonly used ex situ and in situ characterization methods for membranes used as ion conductors in flow batteries (RFBs) are presented. Ex situ characterization methods that can be used to directly determine possible changes of the ionogenic groups in the membrane include ion-exchange capacity (IEC), ion conductivity, and ion permeability. Chemically induced physical and chemical changes that might occur during operation can be quantified using weight losses, molecular weight degradations (e.g. GPC/SEC), TGA, and spectroscopical methods (e.g. FTIR, NMR, or XPS). The physical consequence of the chemical degradation can be further quantified using stress–strain curves, while membrane surface or cross-section changes might be observed using electron microscopy. For the in situ characterization, charge/discharge cycling (CE, VE and EE, discharge capacity, and capacity retention) and open-circuit voltage measurements (OCV – measuring self-discharge) are commonly used, while EIS can be used to determine the membrane resistance.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Conductivity; Discharge capacity; EE; Ex and in situ characterization; Membrane performance; Physical and chemical stability; Redox-flow battery CE; VE